x−2y+2z=−1 2x+y−z=3 3x+2y+z=2 x−2⋅ y+2⋅ z=−1 2⋅ x+y−z=3 3⋅ x+2⋅ y+z=2 x−2y+2z=−1 2x+y−z=3 3x+2y+z=2 Pivot:Riadok1↔Riadok3 3x+2y+z=2 2x+y−z=3 x−2y+2z=−1 Riadok2−32⋅ Riadok1→Riadok2 3x+2y+z=2 −0,333y−1,667z=1,667 x−2y+2z=−1 Riadok3−31⋅ Riadok1→Riadok3 3x+2y+z=2 −0,333y−1,667z=1,667 −2,667y+1,667z=−1,667 Pivot:Riadok2↔Riadok3 3x+2y+z=2 −2,667y+1,667z=−1,667 −0,333y−1,667z=1,667 Riadok3−−2,66666667−0,33333333⋅ Riadok2→Riadok3 3x+2y+z=2 −2,667y+1,667z=−1,667 −1,875z=1,875 z=−1,8751,875=−1 y=−2,66666667−1,66666667−1,6666666666667z=−2,66666667−1,66666667−1,66666667⋅ (−1)=−0 x=32−2y−z=32−2⋅ −0+1=1 x=1 y=−0 z=−1